Metabolic syndrome among type 2 Diabetes Mellitus patients in Ethiopia: a systematic review and meta-analysis - Charkos, Tesfaye Getachew; Lemi, Hunde; Arero, Godana; Getnet, Menberu (Frontiers in Clinical Diabetes and Healthcare, 2024)
IntroductionThe prevalence of metabolic syndrome among type 2 diabetes mellitus patients was inconsistent in Ethiopia. Therefore, we aimed to pool the prevalence of metabolic syndrome among type 2 diabetes mellitus patients using a systematic review and meta-analysis.MethodsPubMed, EMBASE, and Cochrane Library databases were systematically searched for relevant articles from January 2023 to January 2024. In addition, a manual search was conducted using published articles’ reference lists. The random-effects model was used to pool prevalence from individual studies. All analysis was performed using R software.ResultsA total of nine articles met the inclusion criteria and were included in the analysis. The participants’ average age was 59.8 ± 3.84 years old. The pooled prevalence of MetS in T2DM patients was 53% (95% CI: 47–58). A significant heterogeneity was found across the included studies (P < 0.001, I2 = 92%). Based on diagnostic criteria, the prevalence of MetS in T2DM patients was 49% (95% CI: 43–56), 57% (95% CI: 47–67), 57% (95% CI: 43–77), and 44% (95% CI: 20-58) based on IDF, NCEP-ATP II, 2009 harmonized, and WHO criteria. By gender, the prevalence of MetS in T2DM patients was 48% (95% CI: 28–68) for females and 32% (95% CI: 17–49) for males.ConclusionThis study found that over half of type 2 diabetes mellitus patients in Ethiopia are affected by metabolic syndrome, with a higher prevalence observed in females compared to males. The NCEP-ATP II and 2009 harmonized criteria consistently yielded similar prevalence rates of metabolic syndrome. These findings highlight the importance of educating T2DM patients on preventing and managing cardiovascular disease and its related complications.